2017
DOI: 10.18517/ijaseit.7.5.2932
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Phytochemical Characteristics of Local Corn Silk Powder of Three Different Varieties

Abstract: Corn silk is a part of the corn plant that is still considered to be waste from corn processing; however, corn silk is actually known to have the potential to be developed as functional food ingredients and/or nutraceuticals. The potential applications of corn silk are closely related to its chemical composition and the action mechanisms of its bioactive compounds, which have beneficial effects on human health, such as flavonoids and phenolics. This study aimed to investigate the chemical and phytochemical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
(38 reference statements)
1
11
0
1
Order By: Relevance
“…Infusion of corn silk tea (control) contained 68.30 ± 0.41 mg RE/100 g, which was found significantly lowest (P ≤ 0.05) in comparison to all other flavoured corn silk tea. Our finding was almost in range with the study of [36,37] who stated that total flavonoid contents in corn silk teas were ranging from 30.1 to 88.8 μg RE/g. This variation may be due to the extraction procedure differences as well as varietal differences in corn [38].…”
Section: Total Flavonoid Content (Mg Re/100 G)supporting
confidence: 88%
See 1 more Smart Citation
“…Infusion of corn silk tea (control) contained 68.30 ± 0.41 mg RE/100 g, which was found significantly lowest (P ≤ 0.05) in comparison to all other flavoured corn silk tea. Our finding was almost in range with the study of [36,37] who stated that total flavonoid contents in corn silk teas were ranging from 30.1 to 88.8 μg RE/g. This variation may be due to the extraction procedure differences as well as varietal differences in corn [38].…”
Section: Total Flavonoid Content (Mg Re/100 G)supporting
confidence: 88%
“…Nowadays, much attention has been directed towards the identification of plants antioxidant that can be used for human consumption. Corn silk was a by-product of maize, it has been consumed traditionally as a medicine owing to its antioxidant properties, phytochemical ingredients and free radical scavenging activity [35,36].…”
Section: Total Antioxidant Capacity (Mg Te/100 G)mentioning
confidence: 99%
“…Another difference between the silk-entering pathogens may be that U. maydis favours the high moisture and nutrient levels of unpollinated silks, while the other pathogens utilize more carbohydrates in pollinated silks. Varieties of maize have different levels of moisture, ash, protein, fat, and carbohydrate in the silks [77]. Overall, immature, unpollinated silks contain more fat, protein, moisture, macronutrients, and micronutrients than mature silks with fertilised, ripened grain [16].…”
Section: Commonalities and Differences Amongst The Silk-entering Pmentioning
confidence: 99%
“…Chemical analysis was carried out on fibers (soluble, insoluble, and total fiber) using the enzymatic method [19], thermo gravimetric method (loss on drying) moisture content, which is determined by constant temperature and ash is determined. By measuring the muffle furnace [19], protein content using the Micro Kjeldahl method [19], fat content using the Soxhlet method [19] and carbohydrate content using carbohydrate by difference [19] and phytochemical corn silk includes: total phenol [20], flavonoids [11], betasitosterol [21], and antioxidant activity [20].…”
Section: E Analysismentioning
confidence: 99%
“…Corn silk is rich in phenolic compounds, especially flavonoids and natural antioxidant compounds which are high in different amounts and the proportion depends on corn varieties [10]. The local Bisma corn variety has the best phytochemical content compared to the other two varieties, Arjuna and Srikandi Putih [11]. Also showed that the Bisma variety had higher salinity resistance than Arjuna [12].…”
Section: Introductionmentioning
confidence: 99%